A Bibliometric Analysis of Biodiversity Education - Mustafa Derman (Journal of Science Learning, 2023)
The importance of biodiversity is one of the most critical issues today, and intense efforts are being made to protect and maintain biodiversity. In this study, biodiversity, which is related to many disciplines, was evaluated in terms of education. A bibliometric analysis was used. The bibliometric method is widely used to reveal the relationship between scientific studies, the effect of the studies, and the effect of the researchers and journals in a particular field. Research findings showed that many articles have been published on biodiversity recently. In education, out-of-school learning activities are used more widely today. Moreover, the USA, China, and Germany are among the countries that publish more articles about biodiversity. Based on the research findings, it was determined that combining the formal education process with out-of-school activities will help students exhibit positive behavior about the environment and biodiversity. Considering the trend in recent years, studies related to climate change, ecosystem service, sustainability, and citizen science can be carried out.